(untitled) (American Journal of Islam and Society, 2005)
Comparing the responses of Ariel Cohen to those of John Esposito and Graham Fuller makes it crystal clear that promoting the concept of moderate Muslims accords with our previously described struggle between the two Americas: extremism versus ideals. This situation is compounded by the self-contradiction and total confusion of the moderates, who, in their desire to cope with the increasingly unreasonable rather than purely un-Islamic standards, wish to appease the extremists in power and attempt to present an Islam that is acceptable to both Muslims and non-Muslims alike. Instead of elaborating on the supposed “radical ideologies” spread by the “Islamists,” the extremists (Cohen) jump to suggesting that they “should not enjoy the constitutional protections of freedom of religion or free speech.” Still others suggest “in the long term ... the legal activities of Islamists pose as much or even a greater set of challenges than the illegal ones.”1 This is an invitation to open fascism. When a people are not considered fit even for legal activities, their place in society becomes limited to either the concentration camp or the gas chamber. The basis of the extremists’ pre-conditions for being a moderate Muslim is the false assertion that Islam is, in the first place, not moderate. Yet an examination of the criteria being referred to by these non-Muslim paragons shows that many points do not contradict Islam, which ensures that Muslims are moderate by default. This is aptly shown by their general rejection of terror attacks on fellow Muslims of whichever school of thought as well as non-Muslims, whether Christian, Jew, or Hindu. Thus, there is little reason to append moderate to the title Muslim. However, as to the rest of the preconditions employed, these are good enough to take the Muslim out of the bounds of Islam. To them, for example, moderate Muslims should: 1. Not “view the greater Jihad as a pillar of faith, or as a predominant dimension thereof.”2 2. Accept that “the Koran and the Hadith were written for a time and place very different from today” and to question the “origins of Islam.”3 ...